Digital-Based Public Service Innovation from the Perspective of Public Sector Financial Management - Panji Rizki Kurniawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Digital transformation in the public sector has created significant opportunities to reform the way governments deliver services to society while simultaneously managing public finances. This study aims to analyze how digital-based public service innovation interacts with public sector financial management practices in Indonesia. Using a qualitative approach through a systematic literature review, this research integrates various theories and recent empirical findings related to e-government, digital financial governance, and New Public Management. The findings indicate that the digitalization of public services, implemented through platforms such as SIPD, SAKTI, SPAN, and various other e-government applications, significantly improves spending efficiency, budget transparency, accountability in public fund management, and the quality of public services. Nevertheless, the study also identifies several critical barriers that hinder the optimization of this transformation, including disparities in digital infrastructure across regions, low human resource competencies, fragmentation of information systems, and weak cybersecurity regulations. The integration model constructed in this study offers an analytical framework for understanding the relationship between digital service innovation and accountable financial management, with concrete policy implications for bureaucratic reform in Indonesia.